2002
DOI: 10.1007/s00125-001-0730-4
|View full text |Cite
|
Sign up to set email alerts
|

Decreased matrix degradation in diabetic nephropathy: effects of ACE inhibition on the expression and activities of matrix metalloproteinases

Abstract: The accumulation of extracellular matrix (ECM) within the kidney is an ultrastructural hallmark of diabetic nephropathy and is directly linked to a decline in renal function [1]. This increase of ECM can result from either increased synthesis and decreased degradative activity or both. Several studies have shown that high glucose concentration increases synthesis of ECM proteins in both mesangial and tubular epithelial cells [2]. However, more recently it has also Diabetologia (2002) Abstract Aims/hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
84
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 29 publications
13
84
1
4
Order By: Relevance
“…This hypothesis may have a broader significance since AP-1 motifs are important for the expression of the genes encoding several matrix metalloproteinases other than collagenase (Vincenti 2001). These include both MMP-2 and MMP-9 whose glomerula expression, like that of collagenase, is also decreased in type I diabetes (Nakamura et al 1994, McLennan et al 2002. Although the synthesis of MMP-2 was widely considered, in contrast to collagenase and MMP-9, to be independent of AP-1 (Benbow & Brinckerhoff 1997, Westermarck & Kahari 1999, it has recently been shown that MMP-2 is regulated through a non-consensus AP-1 motif that binds members of the AP-1 transcription factor family (Bergman et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis may have a broader significance since AP-1 motifs are important for the expression of the genes encoding several matrix metalloproteinases other than collagenase (Vincenti 2001). These include both MMP-2 and MMP-9 whose glomerula expression, like that of collagenase, is also decreased in type I diabetes (Nakamura et al 1994, McLennan et al 2002. Although the synthesis of MMP-2 was widely considered, in contrast to collagenase and MMP-9, to be independent of AP-1 (Benbow & Brinckerhoff 1997, Westermarck & Kahari 1999, it has recently been shown that MMP-2 is regulated through a non-consensus AP-1 motif that binds members of the AP-1 transcription factor family (Bergman et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although in the streptozotocin rat model of type I diabetes, the glomerula expression of collagenase, MMP-2 and MMP-9 are all decreased (Nakamura et al 1994, McLennan et al 2002, the former MMP is associated with degradation of type 1 collagen whereas type 4 collagen is the principal collagen to accumulate in the glomerulus in diabetic nephropathy (Mauer 1994). Type 4 collagen is a substrate for MMP-2 and MMP-9 (Nagase & Woessner 1999, Brinckerhoff & Matrisian 2002.…”
Section: Multiple Promoter Elements Are Required For the Stimulatory mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to gelatinase B (MMP-9), MMP-2 is not highly expressed in normal or diseased glomeruli (Urushihara et al, 2002). However, it has been shown that renal MMP-2 expression and activity are upregulated by ACE inhibitors in rats with diabetes (McLennan et al, 2002), (Sun et al, 2006). Moreover, Turkay et al reported that the ACE inhibitor enalapril also increased hepatic MMP-2 expression in rats with experimental hepatic fibrogenesis (Turkay et al, 2008), while Westermann et al showed that the ARB irbesartan increased MMP-2 activity in the hearts of mice with cardiomyopathy (Westermann et al, 2007), suggesting that the RAS plays a key role in regulation of MMP-2 expression in the kidney and other tissues.…”
Section: Studies On Ckd Regressionmentioning
confidence: 99%
“…Several studies have shown that high glucose concentration increases synthesis of ECM proteins in both mesangial and tubular epithelial cells. 7 Matrix metalloproteinases (MMPs) are a family of zinc-dependent endopeptidase that mediate the degradation or remodeling of the ECM. 8 The ECM is a multifunctional complex of proteins and proteoglycans assembled in a highly organized manner that contributes to the structural integrity of cells and tissue within an organ system.…”
Section: Introductionmentioning
confidence: 99%